(untitled) (Conferencea, 2022)
We know that cotton is one of the main crops in the world’s agricultural economy, and it has a great role in providing the textile industry with high-quality raw materials. On August 21, President of the Republic of Uzbekistan ShavkatMirziyoyev’s decision No. 3229 "On comprehensive organizational measures for timely and effective cotton defoliation in 2017" was adopted.